Pengaruh Penerapan Model Kooperatif Tipe Teams Assisted Individualization (TAI) Disertai Praktikum Terhadap Hasil Belajar Siswa Pada Materi Ikatan Kimia - Jeivana Laluas; Djefry Tani; Abdon Saiya (Oxygenius Journal Of Chemistry Education, 2022)
This study aims to determine the effect of the implementation of the Teams Assisted Individualization (TAI) cooperative model with practicum on learning outcomes. This study used an experimental method, with a posttest only control design. The population was students of class X IPA and the sample of class X IPA 2, amounting to 26 people as the experimental class and class X IPA 1, totaling 26 people as the control class. The results of the research were analyzed by using the hypothesis (t-test) and the tcount was 1.778> t table 1.67. From these data, it can be influence the application of the cooperative model type TAI along with practicum on student learning outcomes in chemical bonding material.